1998
DOI: 10.1021/jm980368v
|View full text |Cite
|
Sign up to set email alerts
|

Efficacious, Orally Bioavailable Thrombin Inhibitors Based on 3-Aminopyridinone or 3-Aminopyrazinone Acetamide Peptidomimetic Templates

Abstract: We have addressed the key deficiency of noncovalent pyridinone acetamide thrombin inhibitor L-374,087 (1), namely, its modest half-lives in animals, by making a chemically stable 3-alkylaminopyrazinone bioisostere for its 3-sulfonylaminopyridinone core. Compound 3 (L-375,378), the closest aminopyrazinone analogue of 1, has comparable selectivity and slightly decreased efficacy but significantly improved pharmacokinetics in rats, dogs, and monkeys to 1. We have developed an efficient and versatile synthesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 18 publications
1
47
0
Order By: Relevance
“…Pyrazinones have been incorporated into other drug candidate molecules such as inhibitors of human immunodeficiency virus-1 reverse transcriptase (Heeres et al, 2005), caspase-3 (Han et al, 2005), mast cell tryptase (Hopkins et al, 2004), and thrombin (Sanderson et al, 1998). Although metabolism of the majority of the pyrazinone-containing compounds remains unknown, metabolic activation of a series of thrombin inhibitors containing the 6-position substituted pyrazinone was published Singh et al, 2003;Subramanian et al, 2003;Deng et al, 2005;Lin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Pyrazinones have been incorporated into other drug candidate molecules such as inhibitors of human immunodeficiency virus-1 reverse transcriptase (Heeres et al, 2005), caspase-3 (Han et al, 2005), mast cell tryptase (Hopkins et al, 2004), and thrombin (Sanderson et al, 1998). Although metabolism of the majority of the pyrazinone-containing compounds remains unknown, metabolic activation of a series of thrombin inhibitors containing the 6-position substituted pyrazinone was published Singh et al, 2003;Subramanian et al, 2003;Deng et al, 2005;Lin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The small molecule thrombin inhibitor 3-(2-phenethylamino)-6-methyl-1-(2-amino-6-methyl-5-methylenecarboxamidomethylpyridinyl)pyrazinone dihydrochloride (Sanderson et al, 1998) was synthesized in the Pfizer laboratories. Sanderson et al (1998) reported K i values for this compound of 0.8 nM against thrombin and 1800 nM against trypsin. The compound was dissolved to provide a stock solution with a concentration of 20 mg/ml in a combination of 10% ethanol, 10% PEG-400, and 80% sterile saline.…”
Section: Methodsmentioning
confidence: 99%
“…Throm-bin is also a potent platelet agonist, inducing platelet aggregation and possessing smooth muscle cell proliferative properties as well (Coughlin, 2000). Pharmacological attempts have been made at various points of potential intervention in the coagulation cascade, ranging from nonspecific inhibitors such as warfarin, unfractionated heparin, and low-molecular weight heparins, to specific inhibitors of factor Xa or direct acting thrombin inhibitors (Hara et al, 1995;Sanderson et al, 1998;Hauptmann and Sturzebecher, 1999;Pinto et al, 2001). Previous reports suggest that inhibitors of the TF/VIIa complex may prevent thrombosis with a lower bleeding risk than other types of coagulation inhibitors (Harker et al, 1996;Himber et al, 1997;Zoldhelyi et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These inhibitors possessed reactive functional groups such as aldehydes, activated ketones or boronic acids 8 . The non-peptide thrombin inhibitors with a heterocyclic core working as molecules with oral bioavailability gained special attention during the late 1990s decade [9][10][11][12][13] . Recently, Ries et al 14,15 have designed and developed orally active coagulation inhibitors with remarkably low molecular weight containing heterocyclic core structures as potent thrombin inhibitors in vitro.…”
Section: Introductionmentioning
confidence: 99%